PENINGKATAN JANGKAUAN KOMUNIKASI DRONE DENGAN ANTENA MIKROSTRIP SEGIEMPAT MULTI-PATCH 915 MHZ - Badri , Fawaidul (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2024)
This experiment aims to design and test a multi-patatch rectangular microstrip antenna used for enhancing the communication range of drones at a frequency of 915 MHz with an operating frequency range between 902 and 928 MHz. Testing was conducted using CST Studio Suite 2019 simulation software and a Spectrum Analyzer measuring instrument. This antenna uses an Epoxy FR-4 substrate with a dielectric constant (ℰr) of 4.3 and a thickness of 1.6 mm. With this material, the microwave antenna has a radiation element width of 98 mm and a radiation element length of 78 mm. In this study, a multi-patch rectangular microstrip antenna is used because it has a bandwidth characteristic of at least 26 MHz, a maximum VSWR of 2, and a return loss of less than -10 dB. These characteristics are suitable for enhancing drone communication range. The research results indicate that the Multi-Patch Rectangular Microstrip Antenna for enhancing drone communication range at a frequency of 915 MHz has been successfully designed and tested. In conclusion, this Multi-Patch Rectangular Microstrip Antenna, tested using CST Studio Suite 2019 simulation software and a Spectrum Analyzer, can achieve a bandwidth of 152.15 GHz, a VSWR of 1.01, and a return loss of -43.37 dB.